Estudio de métodos de inmovilización alternativos y de bajo costo del hongo Trichoderma sp, para la degradación de compuestos fenólicos. - Pay Casallas, Oscar Felipe (Universidad Antonio Nariño, 2023)
In this research project, different methodologies were evaluated for the immobilization of the fungus Trichoderma sp, in order to degrade phenolic compounds for their possible use in bioremediation processes. This study is of great importance in the field due to the problems that exist today due to phenolic compounds and the interest in removing textile dyes used in the industry, which have been shown to be carcinogenic and mutagenic.